Danza e museo in osmosi: Jérôme Bel al Centro per l’arte contemporanea Luigi Pecci - Chernetich, Gaia Clotilde (Mimesis Journal, 2019)
In 2017, the Luigi Pecci Center for Contemporary Art in Prato presented an exhi- bition, curated by Antonia Alampi, on the French choreographer Jérôme Bel. The exhibition allows to deal with some of the issues concerning the osmosis processes currently underway between dance and museums, where dance is now considered a stable presence within the cultural offer for the public. The relationship between these two worlds, which has increased in the last twenty years and has developed consider- ably thanks to projects such as Boris Charmatz’s Musée de la danse, opens up fundamental questions concerning the creative processes and programming of dance, the status of museums, but also the new methods of choreographic practice and use of art.